Depression, asthma and bronchodilator response in a nationwide study of U.S. adults - Han, Yueh-Ying (J Allergy Clin Immunol Pract, 2015)
BACKGROUND: Little is known about the relation between two common co-morbidities (depression and anxiety) and asthma or bronchodilator response (BDR). OBJECTIVE: To examine the association between depressive symptoms and asthma or BDR in U.S. adults. METHODS: Cross-sectional study of 20,272 adults 20–79 years from the 2007–2012 National Health and Nutrition Examination Survey. Depressive symptoms were measured using the Patient Health Questionnaire (PHQ-9), and classified as: none to minimal, mild, moderate, moderately severe, and severe. Major depression (comprising moderately severe to severe symptoms) was defined as a PHQ-9 ≥15. Anxiety was defined as ≥5 days feeling anxious in the prior month. Current asthma was defined as having been diagnosed with asthma by a doctor or health professional and ≥1 asthma attack in the previous year. BDR (as percentage of baseline FEV(1)) was measured in 1,356 participants with FEV(1)/FVC<0.70 and/or FEV(1)<70% of predicted. Logistic or linear regression was used for the multivariable analysis. RESULTS: Depressive symptoms were significantly and linearly associated with asthma, independently of anxiety symptoms. Subjects with major depression had 3.4 higher odds of asthma than those with minimal or no depressive symptoms (95% confidence interval 2.6–4.5, P<0.01). Among adults with asthma, major depression was associated with a 4.2% reduction in BDR (95% CI=−7.5% to −0.8%, P=0.02). Major depression was not associated with BDR among adults without asthma. Anxiety was not associated with asthma or BDR. CONCLUSION: Depressive symptoms are associated with asthma in adults, independently of anxiety symptoms. Major depression is associated with reduced BDR in adults with asthma.